2021
DOI: 10.1248/bpb.b21-00457
|View full text |Cite
|
Sign up to set email alerts
|

Norisoboldine Attenuates Sepsis-Induced Acute Lung Injury by Modulating Macrophage Polarization <i>via</i> PKM2/HIF-1α/PGC-1α Pathway

Abstract: This study aimed to investigate the effect of norisopoldine (NOR) on acute lung injury in septic mice. Lipopolysaccharide (LPS) was used to establish sepsis induced acute lung injury (ALI) in mice. The dry and wet weight of mice lung was detected, and the pathological changes of lung were observed by hematoxylin and eosin (H&E) staining. Bronchoalveolar lavage fluid (BALF) was detected. Inflammatory factors in BALF were detected by enzyme-linked immunosorbent assay (ELISA). The polarization of macrophages in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 50 publications
(55 reference statements)
2
9
0
Order By: Relevance
“…Cynaroside suppresses hepatic inflammation by inhibiting PKM2/HIF-1α interactions, resulting in decreased activation of HIF-1α target genes and facilitating the transition of M1 macrophages to M2 macrophages [ 118 ]. Norisoboldine hinders the translocation of PKM2 from the cytoplasm to the nucleus, reducing HIF-1α expression and mitigating sepsis-induced acute lung injury [ 119 ]. Additionally, resveratrol enhances endothelial nitric oxide synthase (eNOS) expression and lowers HIF-1α levels to enhance vasodilatory function in a septic shock model [ 125 ].…”
Section: Potential Targeted Drugsmentioning
confidence: 99%
“…Cynaroside suppresses hepatic inflammation by inhibiting PKM2/HIF-1α interactions, resulting in decreased activation of HIF-1α target genes and facilitating the transition of M1 macrophages to M2 macrophages [ 118 ]. Norisoboldine hinders the translocation of PKM2 from the cytoplasm to the nucleus, reducing HIF-1α expression and mitigating sepsis-induced acute lung injury [ 119 ]. Additionally, resveratrol enhances endothelial nitric oxide synthase (eNOS) expression and lowers HIF-1α levels to enhance vasodilatory function in a septic shock model [ 125 ].…”
Section: Potential Targeted Drugsmentioning
confidence: 99%
“…For example, NOR could reduce 2,4-dinitrofluorobenzene-induced dermatitis in mice by inhibiting nuclear factor of activated T-cells (NFAT) ( 92 ). It regulates the polarization of macrophages through the M2 pyruvate kinase (PKM2)/hypoxia-inducible factor (HIF-1α)/peroxisome proliferator activated receptor-γ co-activator 1-α (PGC-1α) pathway, thus alleviating sepsis-induced acute lung injury ( 93 ). It can also inhibit the activation of inflammatory bodies of protein 3 associated with nod-like receptor hot protein domain to weaken the colitis induced by 2,4,6-trinitrobenzene sulfonic acid in mice.…”
Section: Pharmacologymentioning
confidence: 99%
“…Sesquiterpene dimers are a characteristic class of constituents with C 30 cores in L. aggregata, which are plausibly biosynthesized via the coupling of two identical or different sesquiterpenoid molecules (32). Forty-three dimers have been reported, among which lindenane-type sesquiterpenoid dimers are the most representative structures, such as linderaggrenolides A-N (88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101) and linderanoids H-O (109)(110)(111)(112)(113)(114)(115)(116), where linderaggrenolides A-N have an oxygen bridge (32,33). The remaining dimeric sesquiterpene components, such as linderanoids A-G (102-108), include 3 sesquiterpenoid dimers comprising a lindenane and a noreudesmane unit (102-104); 2 dimers consisting of a lindenane and an eudesmane unit (105)(106), and 2 dimers containing a lindenane and an elemanolide unit (107-108) (33).…”
Section: Sesquiterpenoidsmentioning
confidence: 99%
“…A variety of extracts from traditional Chinese medicine (TCM) have been confirmed to possess protective functions in sepsis-induced ALI, such as steroid ruscogenin extracted from Ophiopogon japonicus (L.f.) Ker-Gawl., 27 artesunate extracted from Artemisia annua L., 28 and norisopoldine (NOR) extracted from Lindera aggregata (Sims) Kosterm. 29 Moreover, loganin, one of the best-known iridoid glycosides extracted from Corni Fructus, has been proven to mitigate the sepsis-induced ALI in CLP-induced mice. 30 Our results revealed that CIG reduced the CLP-induced W/D ratio, which indicated that CIG improved pulmonary edema.…”
Section: Cig Attenuated Oxidative Stress In Mice With Sepsis-induced Alimentioning
confidence: 99%